2004
DOI: 10.1111/j.1523-1755.2004.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of extraction and processing of RNA from renal biopsies

Abstract: This study shows optimization of several steps in the protocol for extraction and handling of RNA in renal cortical tissue. RNA extraction and cDNA synthesis can be optimized by the use of the Trizol method and AMV RT, respectively. RNAlater is beneficial for preserving RNA integrity in whole renal cortex during storage and processing, but is not suitable for implementation in routine diagnostic histologic stainings combined with RNA expression studies in dissected biopsy material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…42 Of note, SuperScript III was considerably superior to the first generation of SuperScript (data not shown) that we reported on in a previous study. 43 Finally, we showed that RNA degradation has a major negative impact on mRNA expression levels, which were determined by qPCR. This finding is in line with the highly negative correlation found between the RNA integrity number (RNA quality index or RQI in our study) and the Cq value from the reverse transcriptase PCR assay in earlier studies.…”
Section: Discussionmentioning
confidence: 92%
“…42 Of note, SuperScript III was considerably superior to the first generation of SuperScript (data not shown) that we reported on in a previous study. 43 Finally, we showed that RNA degradation has a major negative impact on mRNA expression levels, which were determined by qPCR. This finding is in line with the highly negative correlation found between the RNA integrity number (RNA quality index or RQI in our study) and the Cq value from the reverse transcriptase PCR assay in earlier studies.…”
Section: Discussionmentioning
confidence: 92%
“…Frozen gastric tissues (100 mg) were normalized in 1 ml TRIzol ® reagent, and total RNA was arranged as previously described (21). The total RNA was measured using a spectrophotometer at 260 nm (VICTOR3; Perkin Elmer, Wellesley, MA, USA), and the RNA was quantified by 1% formaldehyde-agarose gel electrophoresis.…”
Section: Induction Of Gastric Mucosal Lesionsmentioning
confidence: 99%
“…35,36 A third method is the use of preservatives such as RNAlater preservative. [23][24][25][26][27] We demonstrate, for the first time, the concordance in a RHS (the numerical output of a prognostic algorithm) and in the prediction of recurrence when using RNAlater preservative-suspended and snapfrozen tissues (Tables 1 and 2). …”
Section: Rna Integrity and The Sample Handling Problemmentioning
confidence: 99%
“…Ellis and co-workers 25 examined core needle breast biopsies that were snap-frozen or stored in RNAlater preservative. More recently, Alfredson and co-workers 26 isolated RNA from tissues stored in RNAlater preservative, and Roos-van Groningen and co-workers 27 examined the utility of RNAlater preservative in renal cortical tissue. These studies, however, did not systematically compare large numbers of paired tumors (stored in RNAlater and snapfrozen) and most used cDNA arrays of lower densities.…”
mentioning
confidence: 99%